Evaluation of a first of a kind robotic radiation protection technology to reduce scatter exposure during diagnostic procedures and percutaneous coronary interventions - Wojciech E. Krzyzanowski; Pawel Radecki; Marta K. Szczerbińska; Kamil Dawidczyk; Mikołaj Kosek; Krzysztof Romanik; Wojciech Suchcicki; Dariusz Karwowski; Paweł R. Natkowski (American Heart Journal Plus)
Background: This study evaluated the effectiveness of the Radiaction system in providing comprehensive protection to medical personnel during fluoroscopy-guided procedures in an Interventional Cardiology (IC) laboratory. The system confines the imaging beam and blocks scatter radiation at its source, enhancing safety for the Cath lab staff. Methods: A prospective, non-randomized, controlled study compared real-time procedures with and without Radiaction. Sensors were placed around the room and on the main physician to measure radiation exposure during 82 diagnostic and 24 interventional cases without the Radiaction system and 65 diagnostic and 39 interventional cases with Radiaction. Results: Results demonstrated a significant reduction in radiation exposure with the Radiaction system. Across all cases, the overall reduction in radiation was 74.7 % for all sensor locations and 82.9 % for the main physician. Diagnostic procedures exhibited a reduction of 73 % with the Radiaction system and Interventional procedures demonstrated a 79 % reduction across all sensors with the Radiaction system. Calculations were conducted to estimate the reduction during the time that the system was deployed, revealing an 85.7 % reduction across all sensors and 95.1 % for the main physician, reflecting the full potential of the system when used during 100 % of the X-ray time. Users expressed high satisfaction with the system, citing its user-friendly nature, and seamless integration into clinical workflow. Conclusions: The Radiaction system significantly reduced radiation exposure in all cases compared to cases conducted without Radiaction. These findings support the potential of the Radiaction system to offer full-body protection from scattered radiation to all medical personnel in the IC suite, emphasizing its value in enhancing occupational safety in medical environments.